The Role of User-Generated Content and Firm-Generated Content on Destination Image and Intention to Visit Derawan Island: A Stimulus–Organism–Response Approach - Luthfiamer; Maria Apsari Sugiat; Anton Mulyono Aziz (Business Management Research, 2025)
This study examines the role of user-generated content (UGC) and firm-generated content (FGC) in shaping destination image and their influence on the intention to visit Derawan Islands using the Stimulus–Organism–Response (S-O-R) framework. The research addresses the limited understanding of cognitive and affective mechanisms in digital-based destination image formation. A quantitative survey was conducted with 165 potential tourists exposed to UGC and FGC related to Derawan. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that affective image significantly influences intention to visit, while cognitive image is not significant. FGC affects intention both directly and indirectly, whereas UGC influences intention indirectly through affective image. Findings highlight the dominant role of emotional attachment compared to rational evaluation in driving tourist behavior. The study suggests that destination managers should emphasize emotional narratives by balancing UGC authenticity with FGC credibility in digital communication strategies. Future research should explore generational differences or tourist segmentation for broader insights. These results are important as they demonstrate that tourism promotion appealing to emotions is more effective in enhancing visit intentions.